Rancang Bangun Aplikasi Manajemen Koleksi Buku Menggunakan Sql Server dan Arsitektur MVC - Khalifatuniswa, Dyah Meyganizra; Putra, Imamulhakim Syahid (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the increasingly advanced digital era, information technology plays an important role in various industries, including mining and construction. PT. Pamapersada Nusantara District MTBU, as one of the largest mining contractors in Indonesia, faces the need to manage data and information systems efficiently. In this context, the author conducted an internship in the IT department of PT. Pamapersada Nusantara District MTBU with a focus on developing an Android-based book collection application. The purpose of this project is to learn how to connect SQL Server Management Studio with the Model-View-Controller (MVC) architecture, design a book collection management information system, and build an Android application with an MVC architecture to connect to SQL Server. The software development method used is Rapid Application Development (RAD), which focuses on planning, designing, and implementing systems with an object-oriented approach to accelerate the development process. The application developed is able to perform CRUD (Create, Read, Update, Delete) operations on book data and display information in real-time. The use of the MVC architecture ensures a clear separation between business logic, user interface, and data management, thus facilitating application development and maintenance. This application provides two types of user access, namely Admin who has full rights to manage book data and User who can only read and display book data. Although this application is not directly integrated with the operations of PT. Pamapersada Nusantara District MTBU, this project has succeeded in achieving its main goal as a learning tool in developing mobile applications with relevant technology.